Community contexts, socioeconomic status, and meritocratic beliefs and perceptions in China. (July 2021) - Li, Angran; Hu, Anning
Prior empirical research on the relationship between socioeconomic status (SES) and meritocratic attitudes has yielded inconsistent findings. This study contributes to the existing literature by examining the heterogeneous relationship between SES and meritocratic beliefs and perceptions across community socioeconomic contexts in China. Using nationally representative data from the China Family Panel Studies, the results show that individual SES is positively related to support for meritocratic beliefs, but negatively associated with perceptions of meritocracy. Moreover, SES disparities in meritocratic beliefs are more salient in socioeconomically disadvantaged and unequal communities, where residents with relatively higher SES are more likely to hold meritocratic beliefs. In contrast, SES gaps in meritocratic perceptions are more significant in socioeconomically advantaged and homogeneous communities, where individuals with relatively lower SES are more likely to perceive the allocation of resources as meritocratic. These findings provide theoretical insights for understanding how self-interest and system justification theories may jointly explain social origin disparities in public attitudes about meritocracy.